Vania Dutra e Sarah Cabral entrevistam Carlos Alberto Marques Gouveia - Gouveia, Carlos A. M.; Dutra, Vania L. R.; Cabral, Sarah Regina Scotta (Matraga - Revista do Programa de Pós-Graduação em Letras da UERJ, 2022)
Entrevista